Internal Medicine Residents' Perceptions of Pharmacist Involvement in Medical Rounds - Stephanie M. Tubb; Erin B. Loesch (University of Minnesota Libraries Publishing, 2021)
Background: Current physicians note the positive effects of clinical pharmacists on rounds, yet minimal evidence exists regarding medical residents' view of pharmacists in this setting. Knowing their perceptions of clinical pharmacists on acute care rounds will allow pharmacists to optimize their roles and improve their interprofessional interactions. Objective: To assess internal medicine residents' perceptions of pharmacists on rounds, evaluate which recommendations they prefer to receive, and examine their past experiences with pharmacists on rounds. Methods: Internal medicine residents were invited to complete an online survey containing 7 items regarding past experiences with pharmacists on rounds (5-point Likert-type scale; 1=Strongly Disagree, 5=Strongly Agree), 3 items about preferred recommendations (ranking questions), and 6 items regarding perceptions of pharmacy practice (5-point Likert-type scale; 1=Strongly Disagree, 5=Strongly Agree). Data were analyzed using frequencies. Results: 27 residents participated (33.75% response rate). A majority strongly agreed that they always want a pharmacist to be a part of their rounding team (Mean ± SD = 4.93 ± 0.26). They prefer receiving recommendations from the pharmacist in-person before, during, or after rounds and appreciate recommendations on topics such as anticoagulants, antimicrobial stewardship, and renal dose adjustments. Residents did not express a strong knowledge of pharmacists' education and training processes (Mean ± SD = 3.77 ± 1.05), which may have led to their lack of agreement that pharmacists are equipped to be mid-level practitioners (Mean ± SD = 3.00 ± 1.30). Conclusions: Internal medicine residents had positive experiences with rounding pharmacists and desire their involvement on rounds. Pharmacists should make recommendations to residents in-person and educate them on their education and training to allow for further advocacy for pharmacist services.